2019
DOI: 10.9734/ijpss/2019/v31i230206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zeolite and Mineral Fertilizers on Some Soil Properties and Growth of Jew's Mallow in Clayey and Sandy Soils

Abstract: Aims: To evaluate the effect of zeolite and mineral fertilizers on some soil properties, availability of soil nutrients and yield of Jew’s mallow (Corchorus olitorius) in clayey and sandy soils. Study Design: The experimental designed as split plot design with three replicates, the main plots were devoted to zeolite at the rates of 0, 4.76 and 9.52 Mg ha-1 and the sub plots were occupied by mineral fertilizers at the rates of 50% and 100% from the recommended NPK doses. Place and Duration of Study:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…Generally, zeolite is useful for performance and yield of maize due to its high content of nutrients (Table 2). This result is in accordance with those of (DeSutter and Pierzynski, 2005;Bernardi et al 2009;Ahmed et al 2010;Azarpour et al2011;Gomah, 2015 ;Khalifa, et al 2019). Beside, Najafinezhad et al (2015) who concluded that soil addition of zeolite led to increase chlorophyll content (SPAD) and yield of sorghum and corn plant.…”
Section: B-at Harvest Stage (Yield and Measurement Qualitative Traits)supporting
confidence: 88%
See 3 more Smart Citations
“…Generally, zeolite is useful for performance and yield of maize due to its high content of nutrients (Table 2). This result is in accordance with those of (DeSutter and Pierzynski, 2005;Bernardi et al 2009;Ahmed et al 2010;Azarpour et al2011;Gomah, 2015 ;Khalifa, et al 2019). Beside, Najafinezhad et al (2015) who concluded that soil addition of zeolite led to increase chlorophyll content (SPAD) and yield of sorghum and corn plant.…”
Section: B-at Harvest Stage (Yield and Measurement Qualitative Traits)supporting
confidence: 88%
“…This behaviour could be due to that zeolite conditioner holds a high quantity of irrigation water in its pores, where zeolite can retain irrigation water in the root zone to be used by plants when required, thus zeolite helps in resisting the deficit irrigation treatments (I2 and I3) as mentioned by Al-Busaidi et al(2008). It can be said that use of zeolite is one way to improve soil moisture characters and prevent soil moisture losses due to that aluminosilicates is scaffold structure and water molecules occupation in its cavities and removable in its structure so that ion exchange reactions and dehydration do as reversible (Khalifa et al 2019). These findings are in harmony with those obtained by Pisarović et al (2003) who reported that zeolite conditioner can absorb up to 55% water of that can be used in metabolic activities of plants.…”
Section: B-at Harvest Stage (Yield and Measurement Qualitative Traits)mentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolite can be used to improve soil properties under drought, boost the effects of chemical and organic fertilizers (Najafi-Ghiri 2014). The use of zeolite in sandy soils improved soil properties, and nutrients availability and consequently decreased the soil pollution (Khalifa et al, 2019). Also, zeolites assure a permanent water reservoir, providing prolonged moisture during dry periods; they also promote a rapid re-wetting and improve the lateral spread of water into the root zone during irrigation.…”
Section: Introductionmentioning
confidence: 99%